ANALISIS YURIDIS PENEMBAKAN OLEH POLISI TERHADAP PELAKU YANG DIDUGA MELAKUKAN TINDAK PIDANA DIKAITKAN DENGAN ASAS PRADUGA TIDAK BERSALAH - Tabah Santoso; Erdianto Effendi; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Indonesian National Police (INP) is in the Indonesian National Police, which is responsible directly under the President. The Police carry out policing duties throughout Indonesia. Article 18 paragraph (1) of Law No. 2 of 2002 on the Indonesian National Police provides: "public interest Indonesian National Police officers in carrying out its duties and powers can act according to his own judgment". One form of police discretion is often done in the field is in a shoot action against the suspect. Entry shoot on sight against the suspect is situational, ie based on the principle of proportionality in the prevention of violence and firearms should be applied at the time specified by the state police in dealing with individual cases, so that individual action is required pula.Asas presumption of innocence (presumption of innocence) referred to in Article 8 of Law No. 48 Year 2009 on Judicial Power, and also in the general explanation point 3c Criminal Procedure Code, which reads: "Any person suspected, arrested, detained, prosecuted, and / or confronted in the face of the trial court shall be presumed innocent until a court ruling that declared faults and permanent legal power.In practice, investigators action in arresting set out in Article 18 of the Criminal Procedure Code is too excessive and often blamed as a violation HAM.maka the objectives of this study are: First, to determine a violation of the presumption of innocence or not done by the police in practice fire on suspected perpetrators of criminal acts, Second, to determine the responsibility of the police officers who violated procedures in fire on suspected perpetrators of criminal acts. So the author believes that, first it is necessary no specific rules regarding the use of force by the police, so that an act committed by the police there are clear rules and there is also a basic standard of how the use of force does not violate the Human Rights. Second, the police are expected to provide measures sanctions against members of the police who use firearms are not in accordance with the Regulation No. 1 of 2009, and the police institution should enforce the principle of transparency, the officers who commit violations should not be defended, just for the sake of the integrity and reputation of the institution, the police would have the heart to violate human rights , especially when officials violate the presumption of innocence.Keywords: Police Use of Force - Principle of Presumption of Innocence - Human Rights - Justice